2020
DOI: 10.1590/1807-3107bor-2020.vol34.0019
|View full text |Cite
|
Sign up to set email alerts
|

Association of gender, oral habits, and poor sleep quality with possible sleep bruxism in schoolchildren

Abstract: The aim of this study was to verify the oral habits, symptoms, and characteristics of some children aged 8 to 10 years that could be associated with possible sleep bruxism. A cross-sectional study was performed. Questionnaires were sent to parents to obtain information on sex, age, school shift, sleep quality, parents' perception of children's behavior, and children's oral habits (nail biting, object biting, and lip biting), and symptoms such as headache or earache. In addition, parents reported the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
0
10
1
2
Order By: Relevance
“…El diagnóstico y la evaluación clínica del bruxismo es generalmente un proceso complejo que requiere la realización de múltiples pruebas, incluidas observaciones subjetivas y análisis del historial médico, examen clínico, registro de la actividad muscular, electromiografía (EMG) y PSG (Bulanda et al, 2021). El diagnóstico generalmente se realiza en base a informes proporcionados por miembros de la familia, los mismos que describen sonidos característicos que genera el rechinar de dientes mientras duerme (Bulanda et al, 2021;Soares et al, 2020). Kuhn et.…”
Section: Discussionunclassified
“…El diagnóstico y la evaluación clínica del bruxismo es generalmente un proceso complejo que requiere la realización de múltiples pruebas, incluidas observaciones subjetivas y análisis del historial médico, examen clínico, registro de la actividad muscular, electromiografía (EMG) y PSG (Bulanda et al, 2021). El diagnóstico generalmente se realiza en base a informes proporcionados por miembros de la familia, los mismos que describen sonidos característicos que genera el rechinar de dientes mientras duerme (Bulanda et al, 2021;Soares et al, 2020). Kuhn et.…”
Section: Discussionunclassified
“…The prevalence of PB is not well understood. Recent literatures including systematic reviews have reported the regional prevalence of PB (23,24). The highest reported prevalences in the descending order were Finland (40%), United States (37%), Brazil (35%), and Hong Kong (6%) (23,25).…”
Section: Epidemiologymentioning
confidence: 99%
“…SB is not considered a disorder but a risk factor in healthy individuals for a huge number of oral consequences, such as a loss of tooth structure and painful temporomandibular joints (TMJ) and muscles, which can result in a prosthodontic approach [2]. Contrary to the habit of grinding/clenching teeth during some moments of stress that can be stopped or consciousness of the habit can be gained, SB is a behavior totally independent of the conscious control of the child/person being controlled by the central nervous system [3].…”
Section: Introductionmentioning
confidence: 99%
“…The causes (or etiology) of SB remain unknown. Risk factors for SB may include emotional and psychological problems, such as anxiety and stress; personality factors, such as aggressivity; behavioral problems and hyperactivity; and poor sleep, nightmares, and snoring [2][3][4][5]. Concerning sleep quality, pediatric and adolescent bruxers showed a huge incidence of micro-arousals when a polysomnography was performed, which may happen at any stage of the sleep, occurring more frequently in stages 1 and 2 of non-rapid eye movement (REM) sleep [2][3][4]6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation